1998
DOI: 10.1002/mrm.1910400515
|View full text |Cite
|
Sign up to set email alerts
|

In vivo neuronal tract tracing using manganese‐enhanced magnetic resonance imaging

Abstract: Development of efficient imaging techniques to trace neuronal connections would be very useful. Manganese ion (Mn2+) is an excellent T1 contrast agent for magnetic resonance imaging (MRI). Four reports utilizing radioactive Mn2+ in fish and rat brain indicate that Mn2+ may be useful for tracing neuronal connections. Therefore, the purpose of this work was to determine if Mn2+ can be used as an in vivo MRI neuronal tract tracer. The results indicate that topical administration of MnCI2 solution to the naris of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
461
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 430 publications
(480 citation statements)
references
References 29 publications
17
461
1
1
Order By: Relevance
“…In support of this, it has been shown that the transport of Mn 2ϩ is reduced after the administration of the microtubule disrupting agent colchicine (16,29). The speed of axonal transport of Mn 2ϩ is estimated to be approximately 2-6 mm/hour (9,30), in the range of the velocity of fast axonal transport according to Grafstein and Forman (31). In addition to active transport, passive diffusion of Mn 2ϩ may, in theory, contribute to the Mn 2ϩ -enhanced signal observed in the visual pathway.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In support of this, it has been shown that the transport of Mn 2ϩ is reduced after the administration of the microtubule disrupting agent colchicine (16,29). The speed of axonal transport of Mn 2ϩ is estimated to be approximately 2-6 mm/hour (9,30), in the range of the velocity of fast axonal transport according to Grafstein and Forman (31). In addition to active transport, passive diffusion of Mn 2ϩ may, in theory, contribute to the Mn 2ϩ -enhanced signal observed in the visual pathway.…”
Section: Discussionmentioning
confidence: 88%
“…However, such techniques are not applicable to longitudinal studies because they require the study animals to be killed prior to tissue sectioning (9). The ability to perform in vivo serial MRI of CNS axon projections would constitute a major advance in neuroscience, and may in the future provide a diagnostic tool for conditions such as multiple sclerosis (MS), Parkinson's disease, and brain and spinal cord trauma.…”
mentioning
confidence: 99%
“…In contrast to low resolution BOLD-fMRI, MEMRI lends itself to study activity patterns in the brains of small animals at high resolution. In addition to our previous auditory studies (Yu et al, 2005;Yu et al, 2007), MEMRI has also been applied to study odor induced activity in the olfactory bulb (Pautler et al, 1998;Chuang et al, 2006), to examine light adaptation in retinal neurons (Berkowitz et al, 2006), to map cocaine-induced neuronal activation (Lu et al, 2007), and to detect hypothalamic activity (Morita et al, 2003;Chaudhri et al, 2006;Kuo et al, 2006) and ischemia-induced excitotoxicity (Aoki et al, 2003). Furthermore, MEMRI has been validated by correlation with BOLD and CBF (cerebral blood flow) functional maps in the somatosensory cortex of rats (Duong et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…MEMRI is used to trace neuronal connections in vivo in the olfactory and visual pathways of mice and rats (7)(8)(9)(10). However, the method also allows specific brain areas that are active [activation-induced manganese-enhanced (AIM) MRI] to be highlighted, as demonstrated by Lin and Koretsky (11) upon glutamate injection into the common carotid artery.…”
Section: Fmri Methodologymentioning
confidence: 99%
“…The main reason is the difficulty of maintaining the physiological variables within the narrow boundaries dictated by the haemodynamic response. Several common anaesthesia protocols have been used in MEMRI studies, such as ketamine in birds (13) and urethane (33), pentobarbital (7) or isoflurane in mice [e.g. (34)] and songbirds, as safe and ultralight anaesthesia for auditory perception studies (12).…”
Section: Choice Of Anaesthesia and Effect On Brain Activationmentioning
confidence: 99%